2017
DOI: 10.1016/j.tcb.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Physiological Role of Endoplasmic Reticulum-Associated Degradation

Abstract: Many human diseases are associated with mutations causing protein misfolding and aggregation in the endoplasmic reticulum (ER). ER-associated degradation (ERAD) is a principal quality-control mechanism responsible for targeting misfolded ER proteins for cytosolic degradation. However, despite years of effort, the physiological role of ERAD in vivo remains largely unknown. Several recent studies have reported intriguing phenotypes of mice deficient for ERAD function in specific cell types. These studies highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
199
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 187 publications
(224 citation statements)
references
References 84 publications
9
199
0
1
Order By: Relevance
“…This conclusion underscores the importance of an improved understanding of cell type-specific ERAD function in the pathogenesis of many human diseases. While ERAD has largely been studied as a mechanism for clearance of misfolded model substrates (11,12), our findings uncover what we believe to be a novel role of ERAD in the folding of at least a subset of prohormones in endocrine cells under physiological and pathological contexts. Endocrine cells such as AVP neurons are committed and specifically adapted to make specialized prohormones at high levels; however, such high levels may make independent mouse models demonstrate both the significance of ERAD in normal physiology and the potential significance of this pathway in human disease pathogenesis (11,12).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…This conclusion underscores the importance of an improved understanding of cell type-specific ERAD function in the pathogenesis of many human diseases. While ERAD has largely been studied as a mechanism for clearance of misfolded model substrates (11,12), our findings uncover what we believe to be a novel role of ERAD in the folding of at least a subset of prohormones in endocrine cells under physiological and pathological contexts. Endocrine cells such as AVP neurons are committed and specifically adapted to make specialized prohormones at high levels; however, such high levels may make independent mouse models demonstrate both the significance of ERAD in normal physiology and the potential significance of this pathway in human disease pathogenesis (11,12).…”
Section: Discussionmentioning
confidence: 64%
“…Recent studies in mouse models have suggested varying effects of ERAD on the fate of different substrates (11). For example, IRE1α, which is a Sel1L-Hrd1 ERAD substrate in many cell types (20), accumulates in the ER but remains functional to sense misfolded ER proteins in ERAD-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations